The Visual Image of Teachers: A Ten-Country Perspective - Iveta Kestere; Baiba Kalke (Revista Colombiana de Educación, 2015)
Due to the teaching and learning social interaction, an image of teachers is formed within the students’ mind, which is later reproduced in the public space. We understand image as a phenomenon taking place in human consciousness as a result of social experience in the form of sign systems. As the research shows, the teacher’s image in the public space is not always positive. Consequently, the prestige of the profession is negatively affected. In order to understand the mechanism by which the teacher’s image is formed within the collective memory of society, we started a series of studies meant to find out the state of the art. What is the image of a typical teacher according to current students? One of the studies was carried out during the 2011-2012 academic year, under the supervision of university teachers in ten countries –Bulgaria, Greece, Mexico, Pakistan, Serbia, Slovenia, England, South Africa, Turkey and Latvia–. The participants of the study were 1053 students, aged 15. The following components describing the teacher’s visual image were analyzed: gender, age, appearance, verbal and non-verbal communication features. The teacher’s visual image was analyzed in the context of social characteristics of the profession and cultural context. The respondents’ age was also taken into consideration. The study re - vealed how important a teacher’s personality is in students’ life. He/she is a role model. This requirement of society for an ideal person in teaching can create discomfort in real-life teachers. Also, the respondents’ statements about teachers as an extremely important figure in youngsters’ life serve as a basis for increasing the prestige of the teaching profession.